Evaluation of current status of lead toxicity among children: A hospital based cross-sectional study - Ashoka, C; Avinash, T; Rani, S Usha; Venkatesh, T; Venkatesh, T; Abraham, Roy; Kulkarni, M L (Indian Journal of Child Health, 2016)
Introduction: Lead is a highly toxic non-essential metal. Children have a wide spectrum of subclinical and clinical effects due to lead exposure and lead poisoning. Objectives: To identify the extent of the problem of lead toxicity among children and its association with anthropometry, nutritional status and awareness about lead toxicity. Materials and Methods: Study population comprised children admitted in CSI Hospital as inpatients. Purposive sampling was done to enroll patients with no risk of lead exposure. A sample sizeof 100 was calculated using prevalence formula. Anthropometric and blood examinations were done along with knowledge, attitude and practices questionnaire to assess knowledge of caregivers about lead toxicity. Results: A total of 100 children were screened. The mean (standard deviation) blood lead level (BLL) was 7.1 (3.6). 18% of the children demonstrated BLLs of >10 ?g/dl. 19.3% of boys as compared to 15.8% girls had BLL >10 ?g/dl. 36.4% of children belonging to the lower socio-economic status had BLL >10 ?g/dl. The developmental quotient was inversely proportional to the measured BLL. Mean weight, height, and blood indices were lower in thechildren with BLL >10 ?g/dl. The knowledge regarding the adverse health effects of lead toxicity was very poor. Conclusion: Once the early toxic effects are detected before the onset of irreversible changes, the potential victims can be saved. So screening of children for lead toxicity should be made mandatory whenever doubt arises, and since knowledge regarding lead toxicity is poor among caregivers, awareness should be created through health education to the community.